2021
DOI: 10.1037/rep0000387
|View full text |Cite
|
Sign up to set email alerts
|

Perceived injustice in multiple sclerosis: An initial, exploratory study.

Abstract: Purpose/Objective: The current study represents an initial examination of condition-related perceived injustice (PI) in multiple sclerosis (MS) by examining (a) the structural validity and reliability of the Injustice Experience Questionnaire (IEQ) scores and (b) the associations between IEQ scores and scores from measures of anger, pain, depression, anxiety, fatigue, disability, health-related quality of life (HRQOL), physical activity, and sedentary behavior. Research Method/Design: Persons with MS were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…The results of the present study are also consistent with previous research showing significant relations between perceptions of injustice and the severity of pain symptoms [ 18 , 67 69 ]. To date, the relation between perceived injustice and adverse pain outcomes has been demonstrated in individuals suffering from a wide range of painful conditions including whiplash injury [ 18 ], low back pain [ 25 ], catastrophic injury [ 70 ], fibromyalgia [ 71 ], sickle cell disease [ 72 ], osteoarthritis [ 73 ], rheumatoid arthritis [ 74 ], traumatic brain injury [ 75 ], and multiple sclerosis [ 76 ]. It has been suggested that perceptions of injustice might trigger a cascade of cognitive (i.e., rumination), emotional (i.e., anger), behavioural (i.e., pain behaviour) and physical (i.e., muscle tension) reactions that impede recovery of pain conditions [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study are also consistent with previous research showing significant relations between perceptions of injustice and the severity of pain symptoms [ 18 , 67 69 ]. To date, the relation between perceived injustice and adverse pain outcomes has been demonstrated in individuals suffering from a wide range of painful conditions including whiplash injury [ 18 ], low back pain [ 25 ], catastrophic injury [ 70 ], fibromyalgia [ 71 ], sickle cell disease [ 72 ], osteoarthritis [ 73 ], rheumatoid arthritis [ 74 ], traumatic brain injury [ 75 ], and multiple sclerosis [ 76 ]. It has been suggested that perceptions of injustice might trigger a cascade of cognitive (i.e., rumination), emotional (i.e., anger), behavioural (i.e., pain behaviour) and physical (i.e., muscle tension) reactions that impede recovery of pain conditions [ 77 ].…”
Section: Discussionmentioning
confidence: 99%